Pengaruh Kualitas Produk dan Kualitas Pelayanan terhadap Kepuasan Pelanggan pada PT Saricotama Indonesia - Jenny Jenny; Heryenzus Heryenzus (J-MAS (Jurnal Manajemen dan Sains), 2022)
Along with its development, the Coconut Mill industrial company is required to compete with other similar companies so that they can create products with the best specifications for customer satisfaction. This study aims to determine the effect of product and service quality on customer satisfaction of Saricotama Indonesia in Tanjung Batu and Batam at PT Saricotama Indonesia. Customer satisfaction is strongly influenced by the quality of service, along with its determination by product quality. This type of research used is quantitative with a population. The data collection technique was carried out by distributing questionnaires to 150 respondents/consumers to help answer questions on the distributed questionnaire. Then quantitative data analysis was carried out, namely validity and reliability tests, classical assumptions and multiple regression analysis, wherever the hypothesis was tested through t-test and F-test, using the SPSS (Statistical Product and Service Solution) version 22. The results of the study This shows that there is an influence on product quality (X), service (X), and customer satisfaction (Y). The results of the coefficient of determination test show that product quality (X1), service quality (X2) is 5.38 percent, while the remaining 4.62 percent is influenced by other variables not examined in this study.